The use of a “chimeric” autotissue complex from the subscapularis vascular basin for maxillary reconstruction after malignant tumors resection - M. V. Bolotin; V. A. Sobolevsky; I. V. Orlova; I. M. Gelfand; H. Chen (Опухоли головы и шеи)
The objective of this work – to evaluate the results of reconstructive interventions using free revascularized tissue complexes of the scapular region in patients after maxillary resection for malignant tumors. Materials and methods. Between 2014–2020 the post-resection maxillary defects were replaced with free blood-sup plied flaps of the scapular region in 19 patients. In Group 1 (n = 10), the defect was eliminated after total maxillectomy with preservation of the eyeball using a “chimeric” tissue complex, parts of which were positioned in several planes. In Group 2 (n = 9), total and subtotal defects of the hard palate and alveolar process were replaced using a free flap with the inclusion of the scapula angle, which was placed horizontally. The functional and aesthetic results of the reconstructions, the degree of morphological correspondence of the reconstructed structures, as well as the incidence of postoperative complications were assessed. Results. In Group 1 total necrosis of the flap was noted in 2 cases (20 %), in 1 (10 %) case – necrosis of the skin fragment). In Group 2 graft necrosis was observed in 1 (11 %) patient. Satisfactory and excellent aesthetic and functional results were achieved in 6 (60 %) patients in Group 1 and 8 (89 %) patients in Group 2. Conclusion. The scapular flap has a number of advantages for microsurgical reconstruction, including the presence of a long vascular pedicle with large vessels, inclusion of different tissues, possibility of harvesting a “chimeric” version (with significant mobility of parts), low rate of vascular lesions in the area, and most importantly, morphologically close location of bone tissue of the scapula to the maxilla, which ensures successful application of this flap for maxillary repair in patients with advanced cancer of the upper jaw.